Sacral chondroblastic osteosarcoma misdiagnosed as chondrosarcoma and chordoma - Akpolat, Nusret; Yildirim, Hanefi; Poyraz, Kuersat (Tubitak Scientific & Technological Research Council Turkey, 2007)
Chondroblastic osteosarcoma (COS), a subgroup of intramedullary osteosarcoma, is usually located in the knee region of the body. It is most common in adolescents and early adulthood. COS has similar clinical and radiological features to those of conventional osteosarcomas. A 17-year-old male suffered from walking problems and lower limb pain. CT and MRI revealed a mass with soft tissue density and bone destruction at the level of L5-S1. It was described as posttraumatic hematoma. In cytopathologic examination, initial diagnosis was chordoma in fine-needle aspiration cytology (FNAC), chondrosarcoma in incisional biopsy, and finally COS in total resection specimen. Because sacral location of COS is very rare, this report aimed to discuss radiological and pathological diagnostic pitfalls of COS in light of the literature.
Keywords: chondroblastic osteosarcoma; chondrosarcoma; chordoma; sacrum